T6 Vascular smooth muscle derived TRAIL underlies pulmonary vascular remodelling in sugen 5416/hypoxia mice. (December 2018) - Braithwaite, AT; Pickworth, JA; Arnold, ND; West, LE; Iremonger, JE; Thompson, AA; Marriott, HM; Lawrie, A
Abstract : Introduction: Pulmonary arterial hypertension (PAH) is a rare but severe disease characterised by progressive pulmonary arterial remodelling and right ventricular hypertrophy. Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) is a cytokine that promotes proliferation and migration of pulmonary arterial smooth muscle cells (PASMC) in vitro, and is required for PAH in animal models. However, the source of TRAIL and signalling pathways involved in PAH remain to be fully elucidated. Hypothesis: We hypothesised that vascular smooth muscle cell (VSMC)-derived TRAIL is required for development of PAH. Methods: Tamoxifen-inducible smooth muscle myosin heavy chain (smMHC)-Cre-ERT2 mice were crossed with TRAIL fl/fl mice to produce smMHC-Cre-ERT2 tg/0 -TRAIL fl/fl mice with inducible VSMC-specific TRAIL deletion. Mice received tamoxifen or vehicle daily IP injections at 5 weeks of age, prior to inducement of PAH at week 12 by exposure to hypoxia (10% O2) and 20 mg/kg Sugen 5416 weekly for 3 weeks. PAH phenotype was assessed by echocardiography, cardiac catheterisation and histological analysis. To determine a molecular signature of TRAIL stimulation, cultured human PASMC were unstimulated or stimulated with TRAIL for 6 hours. Whole transcriptome was measured by microarray followed by assessment of differential mRNA expression and identification of key pathways. Circulating protein levels of representative genes were measured in patients with PAH and controls. Results: Tamoxifen treated smMHC-Cre-ERT2 tg/0 -TRAIL fl/fl mice were protected from PAH compared to mice lacking Cre expression or vehicle treated mice, without TRAIL deletion. TRAIL-regulated genes in PASMC highlight the focal adhesion KEGG pathway. In PAH patient serum, differences at the protein level were detected in several TRAIL-regulated genes and levels were correlated with clinical severity, providing evidence that these pathways are also perturbed in human disease. Conclusions: We showed that VSMC expressed TRAIL drives the pulmonary vascular remodelling underlying PAH in this model. Ongoing investigations will determine the target cell type and receptor for VSMC-derived TRAIL. Targeting TRAIL has attractive therapeutic potential for PAH.